2016
DOI: 10.1016/j.rse.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Beyond deforestation: Differences in long-term regrowth dynamics across land use regimes in southern Amazonia

Abstract: The loss of tropical forests threatens a broad range of ecosystem services. Particularly, tropical deforestation is a major driver of biodiversity decline and substantial carbon emissions. Regrowth of secondary vegetation may help to restore habitat for many threatened species and improve ecosystem services that deteriorated due to deforestation. However, spatial-temporal patterns of regrowing secondary vegetation in the tropics remain weakly understood. We therefore analyze regrowth dynamics across two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
0
11
0
4
Order By: Relevance
“…Extensive areas of natural regeneration in Amazonia are often observed in areas close to large remnant patches of forest and low intensity of land use (Jakovac et al 2015, Lennox et al 2018. Along a 1000 km stretch of the BR-163 highway, natural regeneration adjacent to forests contributed to 85% and 70% in Pará and Mato Grosso, respectively, of all forest regrowth detected between 1985 and 2012 (Müller et al 2016). Absolute rates of natural regeneration were strongly dependent on the overall amount of deforested area, with higher rates in Pará (maximum of 50% of deforested area) on former pastures with lower management intensity compared to Mato Grosso (maximum of 25% of deforested area) where capitalintensive cropland and pasture systems dominate (Müller et al 2016).…”
Section: Natural Forest Regeneration In the Tropics And Subtropicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive areas of natural regeneration in Amazonia are often observed in areas close to large remnant patches of forest and low intensity of land use (Jakovac et al 2015, Lennox et al 2018. Along a 1000 km stretch of the BR-163 highway, natural regeneration adjacent to forests contributed to 85% and 70% in Pará and Mato Grosso, respectively, of all forest regrowth detected between 1985 and 2012 (Müller et al 2016). Absolute rates of natural regeneration were strongly dependent on the overall amount of deforested area, with higher rates in Pará (maximum of 50% of deforested area) on former pastures with lower management intensity compared to Mato Grosso (maximum of 25% of deforested area) where capitalintensive cropland and pasture systems dominate (Müller et al 2016).…”
Section: Natural Forest Regeneration In the Tropics And Subtropicsmentioning
confidence: 99%
“…Along a 1000 km stretch of the BR-163 highway, natural regeneration adjacent to forests contributed to 85% and 70% in Pará and Mato Grosso, respectively, of all forest regrowth detected between 1985 and 2012 (Müller et al 2016). Absolute rates of natural regeneration were strongly dependent on the overall amount of deforested area, with higher rates in Pará (maximum of 50% of deforested area) on former pastures with lower management intensity compared to Mato Grosso (maximum of 25% of deforested area) where capitalintensive cropland and pasture systems dominate (Müller et al 2016). In the Brazilian Amazon, Conrado da Cruz et al (2020) identified 405 forest restoration projects in 191 municipalities between 1950 and 2017, forest restoration techniques used in descending order of importance were seedling planting, agroforestry systems, assisted natural regeneration, and natural regeneration.…”
Section: Natural Forest Regeneration In the Tropics And Subtropicsmentioning
confidence: 99%
“…These municipalities were selected due to their proximity to the BR-163 highway and their key role in developing the regional agricultural sector. Despite the overall success of Brazil's strategy to reduce Amazon deforestation, forest loss began to rise again after 2012, particularly in municipalities located along the BR-163 [36,37]. A number of studies suggested knowledge gaps in our understanding of how conservation policy incentives affect land-use decisions over time and under changing economic conditions [38][39][40][41].…”
Section: Study Sitementioning
confidence: 99%
“…Recentemente esta região oeste do Pará incorpora-se à expansão do agronegócio, estimulando uma nova frente migratória de produtores capitalizados, principalmente da região Sul do país (CORTÊS; D'ANTONA, 2016). Müller et al (2016) mencionam neste contexto o avanço do desmatamento nesta região, caracterizando o uso da terra mediante a pecuária extensiva.…”
Section: Metodologia áRea De Estudounclassified